The state of the art in medical therapies for pediatric heart failure - Humera Ahmed, MD; Joseph W. Rossano, MD, MS (JHLT Open)
Pediatric heart failure is a rare but serious condition affecting children with congenital heart disease and various forms of cardiomyopathy. The treatment paradigm for pediatric heart failure has historically been shaped by expert consensus guidelines, largely informed by the results of adult heart failure trials. Recently, however, there has been an increased focus on pediatric-specific drug development and clinical trials. Medications such as digoxin, beta-blockers, and renin-angiotensin-aldosterone system inhibitors have been explored in children, but responses can vary based on the underlying heart disease. Newer treatments such as sacubitril-valsartan and sodium-glucose cotransporter 2 inhibitors show promise, but more data are needed to determine their safety and efficacy in young children. This article explores the current state of medical therapy for chronic pediatric heart failure, highlighting the evolution of treatment strategies and the novel therapies under exploration.